Determinants of Antiretroviral (ARV) Treatment Initiation Behavior among People with HIV at Dr. Drajat Prawiranegara Hospital - Neneng Nurhayati; Rita Ramayulis; Ismarina (KHD Production, 2024)
Indonesia is committed to accelerating increased access to treatment in hospitals with quality services. ARV treatment still faces several challenges, such as the level of knowledge of people living with HIV, problems with counseling, assistance, family support, community support, and the number of services available. This study aims to determine the factors associated with the behavior of initiating ARV treatment in people with HIV at RSUD Dr. Drajat Prawiranegara. This type of research is quantitative and has a cross-sectional design. Independent variables are education level, attitude, distance to health services, and family support. Meanwhile, the dependent variable is ARV treatment initiation behavior—the entire population of HIV patients at RSUD Dr. Drajat Prawiranegara in 2023. The total sample was 56 people selected by total sampling. Statistical tests used the Chi-square test with 95% CI and logistic regression tests. The results of statistical tests showed that the variable distance to availability of health services did not have a significant relationship with ARV treatment initiation behavior (p> 0.05), while the variable level of knowledge with p= 0.000, the attitude variable with p=0.009, and the family support variable with p=0.002, which means it has a significant relationship with ARV treatment initiation behavior. The largest OR value is in the knowledge variable OR=12.129.